2022
DOI: 10.1021/acs.jmedchem.2c00094
|View full text |Cite
|
Sign up to set email alerts
|

On the Utility of Chemical Strategies to Improve Peptide Gut Stability

Abstract: Inherent susceptibility of peptides to enzymatic degradation in the gastrointestinal tract is a key bottleneck in oral peptide drug development. Here, we present a systematic analysis of (i) the gut stability of disulfide-rich peptide scaffolds, orally administered peptide therapeutics, and well-known neuropeptides and (ii) medicinal chemistry strategies to improve peptide gut stability. Among a broad range of studied peptides, cyclotides were the only scaffold class to resist gastrointestinal degradation, eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 157 publications
0
22
0
1
Order By: Relevance
“…Macrocyclized D peptides have the potential to address both of these issues 8 . Because they are not recognized by native L-proteases, D peptides display uncommonly long in vivo half lives 54 , and as a result are a privileged peptide drug scaffold. In addition, masking of amide hydrogens through macrocyclization as exemplified by the peptide natural products cyclosporin A 55 , kalata-b1 56 , and the candidate PCSK9 inhibitor MK-0616 57 , can impart potent cell permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Macrocyclized D peptides have the potential to address both of these issues 8 . Because they are not recognized by native L-proteases, D peptides display uncommonly long in vivo half lives 54 , and as a result are a privileged peptide drug scaffold. In addition, masking of amide hydrogens through macrocyclization as exemplified by the peptide natural products cyclosporin A 55 , kalata-b1 56 , and the candidate PCSK9 inhibitor MK-0616 57 , can impart potent cell permeability.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Unlike linear peptides, cyclization can mask the C and N terminus of the peptides that are susceptible to degradation to improve the enzymatic stability in the gastrointestinal tract. [34] Kong et al reported the utilization of phage-based display selection for the design of oral cyclic peptides (Figure 2a). [14] They first synthesized a series of double-bridged peptides using different chemical linkers that impose conformational constraints on the peptide backbone, thus hindering the protease cleavage (Figure 2b).…”
Section: Chemical Modificationsmentioning
confidence: 99%
“…However, the overall absorption promotion of macromolecules by absorption enhancers was still limited [ 9 ], which could be ascribed to absorption enhancers’ inability to offer protection against enzymes and potential toxicity in long-term administration. [ 10 , 11 ] In September 2019, the oral semaglutide tablet entered the market, in which, semaglutide forms a physical complex with the absorption enhancer sodium N-[8-(2-hydroxybenzoyl) amino] caprylate (SNAC) [ 12 ]. Interestingly, besides the traditional effects of changing tight junctions (TJs) or membrane fluidization, the complex of semaglutide and SNAC protects semaglutide against pepsin and augments a concentration-dependent transcellular flux of semaglutide via increasing its solubility through molecular interaction with SNAC.…”
Section: Introductionmentioning
confidence: 99%